Analisis Percepatan Pekerjaan Fondasi Dan Struktur Pada Proyek Konstruksi Pembangkit Listrik Tenaga Uap (PLTU) Tembilahan Propinsi Riau - Swempri Agung Prasetyo; Hendra Taufik; Rian Tri Komara (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The implementation of construction projects often mismatch between the planning schedule and the realization at site like Coal Fired Steam Power Plant Project (PLTU) in Tembilahan has been delayed during construction.. Considering the increasing need of electric energy significantly in electricity system in Indragiri Hilir, therefore the construction of Coal Fired Steam Power Plant Project in Tembilahan must be finished soon. Overall progress (consists of Engineering Procurement Construction) till July 2015 had already reached 65%. In the item of civil construction work until this August 2015 is about 48% so that effort in accelerating the work implementation should be made soon to pursue a delay that until now still have deviation. The acceleration of implementation work was done by some simulations, like in simulation 1 there is no additional workers, simmulation 2 is additional overtime hours, simulation 3 is additional workers and equipment, and also there is additional overtime hours as many as the number of workers and equipments in simulation 4. The analysis is focused on foundation work and the structure of the building/area in which the material already available there and should be installed (erection) because their work is a critical path and directly impact on steam power plant system. From the analysis, it obtained the optimum cost and time that the simulation of 3 get the optimum cost as much as Rp6.377.772.000 and cost performance index (CPI) as much as 0,98 and simulation 4 get optimum time of 183 days and schedule performance index (SPI) of 1,01.Keyword : progress, overtime hour, critical path, optimum cost, optimum time